Design estratégico e inovação para o desenvolvimento de embalagens ecossustentáveis - Camiloti, Lidiane (Universidade do Vale do Rio dos Sinos, 2011)
A major objective of companies is to develop and introduce products with innovative packaging in the market in a short period of time. The ability to create and sustain a competitive advantage, based on the creation of packages with innovative design and strategy, makes this study investigates what are the methods or processes used to develop packages for companies / offices of Design of the western tip of Santa Catarina and seeks to build on the basis of comparison, a proposal for a Strategic Design for the sector, as a matter of bringing back the issue of sustainability. Based on this study, we observed that the packaging and innovative capacity are critical factors in selecting a food product, in addition, we observed that all the characteristics identified in the literature on the packaging are important in their definition. In addition to these findings, it is necessary a detailed study of the characteristics of the Development Process of Packaging held by agencies and offices of Design westernmost region of Santa Catarina, in particular in the cities of Xanxerê, Chapecó and São Miguel do Oeste. The study seeks to contribute to the process of development is improved and more efficient packaging.
Keywords: Embalagens; Design estratégico; Sustentabilidade; Inovação; Tendências; Packaging; Strategic design; Sustainability; Innovation; Trends; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial